Identification of Circulation Flow and Exhibition Layout in the Indonesian Presidential Museum – Balai Kirti, Bogor, through a Narrative Architecture Approach - Wardhana, Arya Wisnu; Wilianto, Herman (Jurnal Arsitektur ZONASI, 2025)
The virtualization of history museums is increasingly prevalent, as technological advancements can no longer be avoided. As a result, the spatial value of history museums is gradually diminishing. This shift is also reflected in changing public trends and behaviors regarding museum visits. To address this phenomenon, narrative architecture emerges as a potential architectural approach that can enhance the value of museums through the unique spatial elements of exhibition spaces, including display arrangements and spatial flow. By implementing narrative architecture, it is expected that a more engaging and immersive storytelling experience can be created through interconnected architectural elements. This research employs a qualitative method by identifying and analyzing the narrative aspects of the Indonesian Presidential Museum – Balai Kirti, located in Bogor City, using the theoretical framework of narrative architecture. The study concludes that, in terms of the building’s connection with its surrounding area and historical context, there is a strong relationship. Internally, each thematic room demonstrates solid integration, as seen in the circulation, atmosphere, exhibition layout, and display objects. Special attention, however, is needed for the circulation between spaces, particularly the outdoor circulation on the second floor. Nevertheless, the overall narrative journey between rooms is well conveyed through the spatial atmosphere and the exhibition design, which gives a monumental yet neutral impression, allowing visitors to experience a coherent and engaging narrative journey.